2014
DOI: 10.1016/j.psychsport.2013.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Self-talk and softball performance: The role of self-talk nature, motor task characteristics, and self-efficacy in novice softball players

Abstract: Objectives: To determine the effect of self-talk on softball throwing performance. Additionally, two moderators, nature of self-talk and type of motor task, as well as a potential mediator of selfefficacy were examined. Design: An experimental, within-subjects, and counterbalanced design. Methods: Forty-two senior high students (mean age = 17.48 ± 0.55) were instructed to use instructional, motivational, and unrelated self-talk with counterbalanced order prior to softball throwing for accuracy and distance tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
28
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 33 publications
7
28
1
Order By: Relevance
“…Some authors have emphasized the need to assess specific measures of self-efficacy [23], but others point out that a general perception of self-efficacy may be an adequate predictor of behavior [26]. Self-efficacy has been deeply analyzed in the sports field, as one of the psychological constructs considered most relevant to athletic performance [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have emphasized the need to assess specific measures of self-efficacy [23], but others point out that a general perception of self-efficacy may be an adequate predictor of behavior [26]. Self-efficacy has been deeply analyzed in the sports field, as one of the psychological constructs considered most relevant to athletic performance [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Chang et al (2014) examined the effect of motivational and instructional selftalk on the performance of the softball launch, and showed that both types of self-talk improved the softball throw performance. Motivational self-talk at higher distances had a great impact on the improvement of performance (13).…”
Section: Introductionmentioning
confidence: 99%
“…This is an open-access article distributed under the terms of the Creative Commons Attribution-NonCommercial 4.0 International License (http://creativecommons.org/licenses/by-nc/4.0/) which permits copy and redistribute the material just in noncommercial usages, provided the original work is properly cited tention, provision of technical information, and introduction of appropriate executive solutions (7,8). Studies by Chang et al Kolovelonis et al and Zourbanos et al respectively in basketball skills, handball, and softball throwing used instructional self-talk techniques to benefit from external attention (9)(10)(11). But, there are also studies that contradict with the results of these studies (12,13).…”
Section: Introductionmentioning
confidence: 99%